Clinical and Radiological Correlates of Unilateral Lower Limb Radicular Pain: An Analytical Study (February 2025) - Dr. Aman Dev Singh,; Dr. Aashish Yadav,; Dr Tsella lachungpa, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: ULLRP is usually blamed on lumbosacral disc pathology, but may also be caused by a dysfunction of the sacroiliac (SI) joints and piriformis syndrome. It is essential to achieve perfect clinical-radiological correlation to prevent any type of misclassification as well as to direct specific therapy. Clinical profile, spinopelvic morphology and MRI in adults with ULLRP who were treated in a tertiary facility at Sikkim, India, were analysed and the relation between lifestyle and work-related variables in the varied ethnic groups of the region was studied. Methods: We recruited a cohort of the Department of Orthopaedics, Central Referral Hospital, Gangtok in a prospective analytical study (May 2023 -December 2024) among adults (>18 years) who were not incapacitated, were in an upright position, and gave consent upon presenting with ULLRP. Exclusions were bilateral radiculopathy, non-ambulatory, spinal deformity, previous lumbosacral, fracture, tumours, malignancy/therapy, hip-pelvic pathology and imaging contraindications. Clinical assessment was standardized VAS (leg), SLR, sitting SLR, slump, FABER, FAIR, and in tests, femoral stretch assessments, plus motor, myotomal and dermatomal testing. Lateral radiographs in the standing positions gave pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS) and lumbar lordosis (LL). The interpretations of MRI (1.5T) were done with ASNR nomenclature; nerve root sleeve angulation (NRSA) was assessed on T1 coronal images (affected side vs unaffected side). Clinical and radiologic profiles were the primary outcomes; lifestyle and occupational correlates were the secondary outcomes. Results: Seventy-five patients (mean age 44.5±12.5 years; 56% female) were analyzed. Mean VAS was 6.7±1.4. IVDP accounted for 76% (L4–L5 36%; L5–S1 36%), with SI joint dysfunction (16%) and piriformis syndrome (8%) comprising the remainder. Sitting SLR and slump tests were significantly associated with IVDP (p=0.001 and <0.001, respectively); the piriformis stress test was positive exclusively in piriformis syndrome (p<0.001). LL differed across diagnoses (IVDP 44.2°±8.4 vs SI 36.9°±12.2 vs piriformis 43.5°±7.6; p=0.045). NRSA was substantially greater on the affected side in IVDP (32.7°±9.4) than in SI dysfunction (16.8°±18.3) or piriformis (7.0°±17.0) and was similarly differentiated on the unaffected side (both p<0.001). Ethnicity, smoking, alcohol use, diet, and occupation showed descriptive differences without statistical significance. Conclusion: In adults with ULLRP, careful synthesis of symptom-limited straight-leg tests with MRI—particularly NRSA—and sagittal alignment improves diagnostic specificity. IVDP predominates at L4–L5/L5–S1, yet SI joint and piriformis etiologies are not rare. LL and NRSA add discriminative value and may refine triage toward conservative care or targeted intervention.